2020
DOI: 10.1103/physrevb.101.094408
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear forward scattering application to the spiral magnetic structure study in εFe2O3

Abstract: The -Fe 2 O 3 magnetic structure has been analyzed using the synchrotron radiation source. Time spectra of nuclear forward scattering for isolated nanoparticles with an average size of 8 nm immobilized in a xerogel matrix have been recorded in the temperature range of 4-300 K in applied magnetic fields of 0-4 T in the longitudinal direction at the European Synchrotron Radiation Facility (ESRF, Grenoble, France). It has been found that the external magnetic field does not qualitatively change the H hf (T) behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The occurrence of iron in the tetrahedral positions is a characteristic of the crystal structure of the spinel, 32 which includes samples 3(2) (spinel phase) and 7. We also note that the tetrahedral environment of iron is observed in orthorhombic sample 8, which has the crystal structure of the ε-Fe 2 O 3 type, 34,35 in which 25% of the cations have a tetrahedral environment. It is noteworthy that the synthesis conditions made it possible to change the tendency for iron to occupy tetrahedral positions in the crystal structure of ε-Fe 2 O 3 .…”
Section: Mössbauer Spectroscopymentioning
confidence: 69%
“…The occurrence of iron in the tetrahedral positions is a characteristic of the crystal structure of the spinel, 32 which includes samples 3(2) (spinel phase) and 7. We also note that the tetrahedral environment of iron is observed in orthorhombic sample 8, which has the crystal structure of the ε-Fe 2 O 3 type, 34,35 in which 25% of the cations have a tetrahedral environment. It is noteworthy that the synthesis conditions made it possible to change the tendency for iron to occupy tetrahedral positions in the crystal structure of ε-Fe 2 O 3 .…”
Section: Mössbauer Spectroscopymentioning
confidence: 69%
“…8,13,14,21 However, some works reported other low-temperature ground magnetic states which resemble features of a canted antiferromagnet with a canting angle different from that above ∼150 K. 8,19 Recently, it was suggested that as a result of strong frustrations of the ε-Fe 2 O 3 magnetic structure, a series of magnetic transitions occur upon cooling from ∼150 K down to ∼80 K, encouraging the formation of non-collinear magnetic arrangement with the magnetic spiral as a ground magnetic state of the system. 75 Moreover, a field-induced transition was witnessed at a temperature interval from ∼50 K to ∼80 K; 76 however, its nature has not been clearly understood yet. In an early study, a metamagnetic transition was suggested to occur at around 50 K; 19 however, no attention has been devoted to systematically study this phenomenon so far and thus, it remains a questionable issue.…”
Section: Resultsmentioning
confidence: 99%
“…Epsilon iron oxide (ε‐Fe 2 O 3 ) nanomagnets are attractive because they have been reported to exhibit a large coercive field and high‐frequency millimeter‐wave absorption at 182 GHz by zero‐field ferromagnetic resonance (the so‐called natural resonance). [ 17–48 ] Metal‐substituted epsilon iron oxide (ε‐ M x Fe 2− x O 3 : M = Al 3+ , Ga 3+ , and In 3+ ) and Ti 4+ −Co 2+ cosubstituted series, ε‐(TiCo) x Fe 2− x O 3 , exhibit zero‐field ferromagnetic resonance over a wide frequency range of 35–182 GHz. Rhodium‐substituted epsilon iron oxide, ε‐Rh x Fe 2− x O 3 , shows even higher resonance frequencies above 182 GHz by increasing the Rh/Fe ratio.…”
Section: Introductionmentioning
confidence: 99%